Pengembangan Sosio Chemoentrepreneurship dalam Produksi Bahan Kebutuhan Rumah Tangga Berbasis Sodium Lauril Sulfonat di Desa Aik Dareq Kabupaten Lombok Tengah - Ahmadi Ahmadi; Sri Nopita Primawati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This service activity aims to provide chemical skills coaching in the community in producing various household needs which are the basic ingredients of Sodium Lauril Sulfonate such as detergents, dish soap and hand soap. This activity is carried out during a pandemic by complying with health protocols. Methods of this activity include: (1). Initial Program Initiation, (2). Organization Creation, (3). Assistance in Manufacturing, packaging and marketing of various household products made from sodium lauryl sulfonate. The youth group who participated in the activity was first given an understanding of the tools and materials that would be used in the manufacture of products. After the youth group understood, only then did the team enter the coaching stage. The final stages of this activity were liquid detergent, dish soap and hand soap. This activity is very important because it relates to skills as a participant's capital in meeting the demands of the world of work, besides in community production, it will also be taught in the marketing and evaluation system. So the community will make various products needed, market them, and they can enjoy the benefits as additional income.